Crystal structure and Hirshfeld surface analysis of a bromochalcone: (E)-1-(3-bromophenyl)-3-(2,6-dichlorophenyl)prop-2-en-1-one - S. Bindya; C. S. Chidan Kumar; S. Naveen; B. P. Siddaraju; Ching Kheng Quah; Md. Abu Raihan (Acta Crystallographica Section E: Crystallographic Communications, 2019)
In the title chalcone derivative, C15H9BrCl2O, the aryl rings are inclined to each by 14.49 (17)°, and the configuration about the C=C bond is E. There is a short intramolecular C—H...Cl contact present resulting in the formation of an S(6) ring motif. In the crystal, the shortest intermolecular contacts are Cl...O contacts [3.173 (3) Å] that link the molecules to form a 21 helix propagating along the b-axis direction. The helices stack up the short crystallographic a axis, and are linked by offset π–π interactions [intercentroid distance = 3.983 (1) Å], forming layers lying parallel to the ab plane. A quantification of the intermolecular contacts in the crystal were estimated using Hirshfeld surface analysis and two-dimensional fingerprint plots.